Applying Cold Atmospheric Plasma to Preserve the Postharvest Qualities of Winter Jujube (Ziziphus jujuba Mill. cv. Dongzao) During Cold Storage - Jin, Tao; Dai, Chenwei; Xu, Yong; Chen, Yan; Xu, Qinghua; Wu, Zhengwei (Frontiers in Nutrition, 2022)
Winter jujube (Zizyphus jujuba Mill. cv. Dongzao) is a very popular horticultural fruit worldwide, which contains a high number of bioactive compounds. Nevertheless, jujube is perishable by microbial contamination and has a short shelf life under non-controlled conditions. Cold atmospheric plasma (CAP) presents a great potential for food sterilization, maintain postharvest quality, and prolong storage time. Herein, this study investigated the potential effect of CAP with different exposure time (0, 5, 10 and 20 min) on the physicochemical and biochemical changes of jujube during 15-d storage at 4 ℃ 90 % relative humidity. The results showed that CAP treatment could obviously delay ripening, but displayed no effects on the speed of weight loss and moisture content. Meanwhile, the total native aerobic bacterial count in each jujube group was restrained during whole storage. However, CAP treatment showed a time dependent manner to improve genes expression (PAL, 4CL, DFR, ANS, LAR and ANR) related to phenolics biosynthesis. As compared with other groups, 20-min CAP treatment can keep or increase total phenolic content (TPC), maintain antioxidant activity and reduce oxidative damage. Furthermore, the hydrogen peroxide (H2O2) and malondialdehyde (MDA) content in jujube during middle storage were visibly reduced by 20-min CAP treatment. All in all, our findings concluded that appropriate CAP exposure time can be a promising candidate for the postharvest preservation of jujube.